Entre policía, iglesia y conformismo doméstico el fotoreportage social y familiar en la España de Franco - Rius, Nuria F. (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
In the first period of the Franco dictatorship (1940-1960), the photographic practice grew in a wide range of typologies both professional and domestic. This article explores an intermediate form that I categorise as "social and family photo-reportage". This refers to a commercial genre with the aim of documenting the institutional and social conformism in the Francoist communal and family life through profane and religious ceremonies (dsuch as marriages, public processions, banquets). My research draws from this type of domestic photography to analise it as a complex phenomenon within its production stage. Seen from this perspective, the subject of study is, on one hand, the boom of 35mm cameras and the new wave of amateur photographers who found in photo-reportage a further and complementary source of income in the precarious economic context of the period. On the other hand, the tension between photografy and public space, under strict photographic licences managed by the police and the Spanish Church. [...]